Addressing Energy Performance Challenges in a 24-h Fire Station Through Green Remodeling - June Hae Lee; Jae-Sik Kang; Byonghu Sohn (Buildings)
This study presents a comprehensive case of green remodeling applied to a local fire station in Seoul, South Korea. The project aimed to improve energy performance through an integrated upgrade of passive systems (exterior insulation, high-performance windows, and airtightness) and active systems (electric heat pumps, energy recovery ventilation, and rooftop photovoltaic systems), while maintaining uninterrupted emergency operations. A detailed analysis of annual energy use before and after the remodeling shows a 44% reduction in total energy consumption, significantly exceeding the initial reduction target of 20%. While electricity use increased modestly during winter due to the electrification of heating systems, gas consumption dropped sharply by 63%, indicating a shift in energy source and improved efficiency. The building’s airtightness also improved significantly, with a reduction in the air change rate. The project further addressed unique challenges associated with continuously operated public facilities, such as insulating the fire apparatus garage and executing phased construction to avoid operational disruption. This study contributes valuable insights into green remodeling strategies for mission-critical public buildings, emphasizing the importance of integrating technical upgrades with operational constraints to achieve verified energy performance improvements.